OP0046 Risk factors for adverse pregnancy outcome in antiphospholipid antibodies carriers: results from a multicenter italian cohort over 20 years of experience. (15th June 2017) - Lazzaroni, MG; Andreoli, L; Chighizola, CB; Ross, T Del; Gerosa, M; Kuzenko, A; Raimondo, M-G; Lojacono, A; Ramazzotto, F; Zatti, S; Trespidi, L; Meroni, PL; et al.
Abstract : Background: Antiphospholipid antibodies (aPL) are risk factors for Adverse Pregnancy Outcome (APO). In particular, for aPL carriers (patients with aPL positivity with no thrombotic or obstetric history) pregnancy outcome and treatment are still undefined. Objectives: To review pregnancy outcome in a large multicenter cohort of aPL carriers patients, according to different serological profile and treatment protocols. Methods: We reviewed 69 pregnancies in 61 patients, prospectively followed in 3 Italian centers (1994–2015). Patients with any complication in previous pregnancies or concomitant autoimmune diseases were excluded. aPL profile was defined as the combination of the 3 criteria tests for aPL (Lupus Anticoagulant, anti-cardiolipin, anti-Beta2 Glycoprotein I). APO was defined as: miscarriage (<10w), fetal death (≥10w), severe preterm delivery (≤34w) with or without preeclampsia (PE), HELLP syndrome or perinatal death. Results: Regarding aPL profile: 44 (64%) were single positive, 16 (23%) were double and 9 (13%) were triple. aPL non-criteria manifestations were present in 6 (9%) and lupus-like manifestations in 5 (7%). Eight pregnancies had a combination treatment with prophylactic low molecular weight heparin (LMWH) plus low dose aspirin (LDA), 37 had LDA alone and 24 had no treatment. We observed 2 thrombotic events (3%, 1 deep venous thrombosis and 1 ischemic stroke) and 6 APO (9%): 3 fetal deaths and 3 pre-term birth ≤34w with PE. We compared 8 complicated (6 APO, 2 thrombosis) with 61 non-complicated pregnancies (Table 1 ). Acquired risk factors (p:0.006), non-criteria aPL (p:0.018) and lupus-like manifestation (p:0.010), triple positive aPL profile (p:0.001) were associated with APO. The combination treatment was also more frequent in APO pregnancies (p:0.005). Conclusions: Acquired risk factors, aPL profile (triple positivity), lupus-like and non-criteria aPL manifestations could represent risk factors for pregnancy complications and could determine failure to conventional treatment.These patients may deserve additional treatment, for example LMWH at higher/anti-coagulant dose or immunomodulatory treatment (e.g.hydroxychloroquine, also considering its anti-platelet/anti-thrombotic effects). Disclosure of Interest: None declared